1987
DOI: 10.1126/science.3107122
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Rapidly Increases Diacylglycerol by Activating De Novo Phosphatidic Acid Synthesis

Abstract: The mechanisms whereby insulin increases diacylglycerol in BC3H-1 myocytes were examined. When [3H]arachidonate labeling of phospholipids was used as an indicator of phospholipase C activation, transient increases in [3H]diacylglycerol were observed between 0.5 and 10 minutes after the onset of insulin treatment. With [3H]glycerol labeling as an indicator of de novo phospholipid synthesis, [3H]diacylglycerol was increased maximally at 1 minute and remained elevated for 20 minutes. [3H]Glycerol-labeled diacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(85 citation statements)
references
References 23 publications
9
76
0
Order By: Relevance
“…22,33 Furthermore, although proximal tubules do not metabolize glucose (they are gluconeogenic), they can metabolize fructose and form diacylglycerol, one of the activators of PKC. 29,30,34,35 In agreement to this possibility, our results show that the effects of fructose can be blunted by PKC inhibition. Finally, fructose might modify the surface expression of NHE3.…”
Section: Hypertensionsupporting
confidence: 78%
See 1 more Smart Citation
“…22,33 Furthermore, although proximal tubules do not metabolize glucose (they are gluconeogenic), they can metabolize fructose and form diacylglycerol, one of the activators of PKC. 29,30,34,35 In agreement to this possibility, our results show that the effects of fructose can be blunted by PKC inhibition. Finally, fructose might modify the surface expression of NHE3.…”
Section: Hypertensionsupporting
confidence: 78%
“…28 Third, fructose metabolism might generate secondary metabolites, such as diacylglycerol, that further activate PKC. [29][30][31][32] It has been shown that the stimulatory effects of angiotensin II on proximal tubule transport are mediated by PKC activation. 22,33 Furthermore, although proximal tubules do not metabolize glucose (they are gluconeogenic), they can metabolize fructose and form diacylglycerol, one of the activators of PKC.…”
Section: Hypertensionmentioning
confidence: 99%
“…The activated receptor kinase phosphorylates its primary substrate, IRS-1, on YMXM motifs, thus converting IRS-1 into a docking protein for SH2 domain-containing proteins such as phosphatidylinositol 3-kinase or Grb2 [11]. Insulin stimulation has been reported to cause diacylglycerol levels to increase in several cell types [12,13]. The possibility that this increase is mediated by phospholipase Cy is suggested by the finding that insulin stimulates the activity of this enzyme in plasma membrane preparations [14].…”
Section: **Present Addressmentioning
confidence: 97%
“…Lipids were extracted and DAG was purified by thinlayer chromatography [6,8,11], and counted for radioactivity. DAG content of lipid extracts was measured by the DAG kinase method (Lipidex) of Preiss et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…The DAG which derives from phospholipase Cmediated hydrolysis of phosphatidylinositol 4',5'-bisphosphate (PIP2) [3] causes PKC to translocate from cytosol to the membrane, and this serves as evidence of PKC activation [4]. Some agonists, such as insulin, do not stimulate PIP2 hydrolysis significantly, but increase DAG through enhanced synthesis of phosphatidic acid (PA) de novo [5][6][7][8][9][10][11], and hydrolysis of a phosphatidyl- inositol (PI)-glycan [12] and phosphatidylcholine [11,13,14]. Insulin stimulates PKC translocation [15], but it is uncertain whether DAG derived from the de novo pathway contributes to this activation.…”
Section: Introductionmentioning
confidence: 99%